Development Of Multimodal Gamified Drakocan For Indonesian Drama Learning: Pengembangan Media Gamifikasi Multimodal Drakocan Untuk Pembelajaran Drama Bahasa Indonesia - Ary Martina; Muhamad Sofian Hadi; Fajar Suharmanto (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Digital technology integration has become an essential component of contemporary elementary education to support student-centered and interactive learning environments. Specific Background Indonesian language drama instruction at the elementary level commonly relies on conventional text-based methods, resulting in low student engagement and limited comprehension of dramatic elements. Knowledge Gap Previous instructional media generally utilize audio or visual components separately, with limited integration of gamification and multimodal approaches in drama learning contexts. Aims This study aims to develop a multimodal-based gamification learning medium named Drakocan for Indonesian drama instruction in Grade VI elementary schools. Results The development employed the ADDIE model and involved expert validation and staged field trials, producing high validation scores from language, material, and media experts, as well as positive feasibility evaluations from students in one-to-one, small group, and field group trials, accompanied by higher posttest scores compared to pretest results. Novelty The study introduces a single integrated learning medium combining gamification elements with audio, visual, and textual modes for elementary drama learning. Implications The findings indicate that multimodal gamification media can serve as an alternative instructional approach aligned with curriculum demands and active learning practices in elementary Indonesian language education. Highlights • Multistage validation confirmed strong suitability across expert and learner evaluations• Learning activities integrated gameplay progression with narrative-based instructional content• Assessment results demonstrated consistent score gains following media use Keywords Multimodal Learning; Gamification Media; Drama Learning; Indonesian Language Education; Elementary School